Student Perceptions of Online Engagement - Petrea Redmond; Megan Alexsen; Suzanne Maloney; Joanna Turner; Alice Brown; Marita Basson; Linda Galligan; Jill Lawrence; Robyn Henderson (Online Learning, 2023)
This paper reports on research that extends knowledge about higher education students’ perceptions of online engagement. In particular, the study aimed to identify what students thought engagement was and how they experienced it. Understanding students’ views about online engagement will provide a more comprehensive understanding of the topic and should assist instructional designers to support academic staff to develop online courses that are more likely to engage their students. Using a mixed-methods approach, the study found that students felt most engaged with learning when doing practical, hands-on activities. Additional findings from the qualitative and quantitative data are highlighted, with some differences between the students’ perceptions in the different types of data, particularly concerning social engagement. This suggests that further research is warranted. The paper offers several practical implications for student learning.